Basic concepts for simple and complex liquids - Barrat, Jean-Louis 1964- (Cambridge University Press, 2003)
Presenting a unified approach to the liquid state, this book focusses on the concepts and theoretical methods that are necessary for an understanding of the physics and chemistry of the fluid state. The authors do not attempt to cover the whole field in an encyclopedic manner. Instead, important ideas are presented in a concise and rigorous style, and illustrated with examples from both simple molecular liquids and more complex soft condensed matter systems such as polymers, colloids, and liquid crystals. After a general chapter introducing the liquid state, the book is in four parts devoted to: thermodynamics; structure and fluctuations; phase transitions, interfaces and inhomogeneous fluids; and, finally, transport and dynamics. Each chapter introduces a new set of closely related concepts and theoretical methods, which are then illustrated by a number of specific applications covering a broad range of physical situations.